A Cognitive-Pragmatic Study of Irony Response - Zhang Ying (European Scientific Journal, ESJ, 2016)
As the second part of an irony-irony response (I-IR) adjacency pair, an IR is based on the perception of irony. It affects the ironist and plays a significant role in shaping the communicative effect of irony as well as the nature of the ongoing conversation. Therefore, IRs reflect people’s employment of communicative strategies and deserve pragmatic attention. Within the framework of Sperber and Wilson’s relevance theory (RT), the author views IRs as illocutions with different relevance degrees chosen by reactors to perform certain perlocutionary acts and probes into the variety of IR strategies and motivations from a cognitive-pragmatic aspect. As is found, IRs can be simple and complex illocutions with various relevance degrees: maximally relevant, very relevant, weakly relevant and irrelevant. In responding to irony, people are inclined to perform simple relevant acts rather than supplying irrelevant reactions. Moreover, the familiarity degree between the interlocutors overweighs the content of irony in affecting reactors’ motivations and hence their response choices.